Pemberian Literasi Digital Marketing dan Pendampingan Penjualan Produk UMKM di Lampung melalui Aplikasi Platform Digital, Periklanan dan Konten Marketing - Mahrinasari MS; Remy Yudha Saputra; Ayu Gita Permata; Apridalia Apridalia; Haysi Muliyana; Lusia Dewi Sulistiati; M. Fahrudin (IKIP PGRI Bojonegoro, 2024)
ABSTRACTThe Community Service Activities carried out are Providing Digital Marketing Literacy and Product Sales Assistance to MSMEs through the Digital Platform Application, Advertising, and Marketing Content with the aim of providing the community, especially MSME business actors, with literacy related to digital marketing and can increase sales of their products using the Digital Platform so that they can open up opportunities to increase customer potential with